PENGENDALIAN SURAT MASUK MENGGUNAKAN APLIKASI SISTEM INFORMASI KEARSIPAN DINAMIS (SIKD) di SUBBAGIAN PERSURATAN DAN ARSIP AKTIF PADA ARSIP NASIONAL REPUBLIK INDONESIA - Mungky Hendriyani (KOMPLEKSITAS: JURNAL ILMIAH MANAJEMEN, ORGANISASI DAN BISNIS, 2020)
The current rapid technological development can cause many government and private institutions or agencies to make changes by changing previous work patterns. Initially it could only be done manually, now you can switch to using electronic media so that work can be done better, for example in the form of an archive management application. The National Archives of the Republic of Indonesia as a national archival institution builds a National Archives Information System to support the efficient and effective implementation of the National Archives System. ANRI builds computer software in the form of applications. The application, hereinafter referred to as the Dynamic Archival Information System Application (SIKD)